Dynamic changes in gut microbiota during pregnancy among Chinese women and influencing factors: A prospective cohort study - Li, Muxia; Zhang, Guohua; Cui, Lijun; Zhang, Lin; Zhou, Qian; Mu, Chenxue; Chi, Ruixin; Zhang, Na; Ma, Guansheng (Frontiers in Microbiology, 2023)
Gut microbiota (GM) dynamics during pregnancy vary among different populations and are affected by many factors, such as living environments and diet. This study aims to observe and evaluate the changes in the structure and function of the GM from the first to the third trimester of pregnancy in Chinese women, and to explore the main factors affecting the changes in intestinal microecology. Fifty-five Chinese pregnant women were recruited for this study and their fecal samples were collected during the first (P1), second (P2), and third trimesters (P3) of pregnancy. We exploited metagenomic sequencing to compare the composition and function of the GM in different pregnancy periods. Bioinformatic analysis revealed that there were differences in the composition of the GM among P1, P2 and P3, as indicated by the increase in α-diversity and β-diversity of the GM and the differences in the relative abundances of distinct bacterial phyla. Gestational diabetes mellitus (GDM) was the main factor (P＜0.05) that affected the changes in GM at various stages of pregnancy. There were also disparities in the structure of the GM between the GDM group and non-GDM group in the P1, P2, and P3. The GDM group exhibited increased abundances in Ruminococcus_gnavus, Akkermansia_muciniphila, Alistipes_shahii, Blautia_obeum and Roseburia_intestinalis; While, the abundances of Bacteroides coprocola, Bacteroides plebeius, Erysipelatoclostridium ramosum and Prevotella copri were increased in the non-GDM group. Three of the four species enriched in the non-GDM group manifestied significantly negative correlations with the insulin-signaling pathway and lipopolysaccharide biosynthesis (r ≤-0.3, adjusted P < 0.05). In the GDM group, B. vulgatus and R.gnavus were significantly and positively correlated with insulin signaling pathway and lipopolysaccharide biosynthesis (r ≤-0.3, adjusted P < 0.05) among the species enriched from early pregnancy. Virtually all of the species enriched in P2 and P3 were positively correlated with steroid hormone biosynthesis. These results suggest a potential role for the GM in the development of GDM, enabling the potential prevention of GDM by targeting the GM.